FISH DIVERSITY OF RIVERS OF KARNATAKA - MOGALEKAR, H. S.; JAWAHAR, P.; CANCIYAL, J. (Journal of the Inland Fisheries Society of India, 2021)
The checklist of the riverine fishes of Karnataka includes 240 species (109 species from Cauvery, 59 species from Godavari, 168 fish species from Krishna and 124 fish species from West flowing river basins) distributed under 102 genera, 38 families and 14 orders. The top three orders with diverse species composition were Cypriniformes (140 species, 45 genera and 5 families), Siluriformes (51 species, 24 genera and 9 families) and Perciformes (26 species, 15 genera and 9 families). Fourty species listed under threatened category including 5 species as critically endangered, 22 as endangered and 13 as vulnerable. Selective breeding and ranching of native fish species might help to overcome the problems of species endangerment.Keywords: Riverine fish fauna, conservation status, Karnataka